Dois métodos de fixação externa para osteossíntese de tibiotarso em galinhas (Plimouth rock-white) : modelo experimental para uso em aves selvagens - Conti, Juliano Bortolo de (2005)
This paper aims to evaluate the use of type I and II skeletal external fixator for tibiotarsal fractures treatment in hens (Plimouth rock-white). Sixteen adult fowls were used. They were randomly divided into two groups where type I and II skeletal external fixators were used. The fowls were pre-anesthetized with morphine sulphate, induced and anesthetized with halothane, then, a fracture was made onto the right tibiotarsus by using a floating saw in the diafisys of the member. Four Kirschener pins two proximal and two distal to the fracture core were inserted through both osseous cortical and, after reducing the fracture externally connected by an auto-polimerizable acrylic bar one on the lateral and the other on the medial side of the member of Group II. The average time and the mean deviation for the osseous cicatrization evaluated by X-rays was 40,37+11,8 days for Group I and 35,12 + 8,72 days for Group II (p>0,05). The average time and mean deviation for reestablishment of the regular walking was 24 + 16,42 days for Group I and 20 + 7,09 days for Group II. Statistically, there was a better performance by Group II in comparison to Group I walking reestablishment. The overcomes for this experiment show open reduction and type II external skeletal fixator application to be an effective method for treating tibiotarsus fractures in hens (Plimouth rock-white), however, type I external skeletal fixator application did not demonstrate to be fully satisfactory in fracture treatment leading to pin migration in 25% of the fowls.